The role of assault severity, rape myth beliefs, personality factors, attribution style and psychological impact in predicting coping with rape victimization - Mgoqi, Nolwandle Codelia (My University, 2007)
This study is aimed at understanding the role of assault severity, personality traits and rape myths in predicting rape victims’ psychological responses and coping styles. Specifically, the study assessed the mediating role of victims’ attribution in predicting psychological impacts of rape victimization and the coping styles. On the basis of theory, it was postulated that the severity of assault (as determined by either the use of physical force and/or the presence of weapons); intrapersonal resources of hardiness; and the acceptance of rape myths would have a direct influence on survivors’ psychological impact and on coping. The thesis provides comprehensive coverage of the prevalence of rape victimization; the trauma and psychological impacts of rape victimization; coping with rape victimization; and the theory on the role of social cognition (appraisal and attribution) in explaining victims’ responses to rape. The theoretical conceptualisation underpinning the study offers a unique integration of this body of knowledge within the South African context. In investigating the research question, two hundred and fifty adult black (African) South African women who had experienced rape in the previous month were interviewed about the event and their subsequent responses. The interviewees were drawn from Xhosa, SePedi and Zulu speaking communities. The study was located within the quantitative research tradition. A structured interview questionnaire was developed. Descriptive statistics were calculated and the emphasis of the analysis was in the area of the Structural Equation Model. The model was successful in terms of explained variance in accounting for the two types of coping; approach and avoidance coping dimensions followed by the psychological impact and attribution. The results showed psychological impact as explained through the symptoms of Hyperarousal, Intrusion and Avoidance had the greatest influence on coping of rape survivors. As hypothesized, the results confirmed that an increase in rape assaults severity resulted into increased levels of psychological distress. The findings indicated that internal styles of self-blame attribution (behavioural and characterological attribution) were prevalent among victims of rape in the present study. Although hardiness (commitment and control) dimensions were not found to significantly influence coping, an orientation of control and commitment amongst survivors was found to significantly influence the attribution styles. Furthermore, the control dimension was found to have a significant influence on victims’ psychological distress. Interestingly, the results revealed that acceptance of rape myths among survivors resulted in a decrease in psychological distress. The findings demonstrate the strength of the current study in the development and testing of theoretically based models of processing rape victimization recovery among rape survivors. The implications of the data are explored.
Student Number : 0500547G - PhD thesis - School of Psychology - Faculty of Humanities
Keywords: rape; coping; rape myths; assault; severity; African women; hardiness; psychological impact